The Chicago Martyrs. The famous speeches of the eight anarchists [A. Spies, M. Schwab, O. Neebe a.o.] in Judge Gary's Court, Oct. 7,8,9, 1886, and "Reasons for pardoning Fielden, Neebe and Schwab", by J.P. Altgeld. [Introd. by Wm Holmes] (San Francisco, 1899)
Free society library, 1 - May, 1899. In: A.T.V. Spies, Reminiscenzen. Eine rede vor Richter Gary, ...